Scaling-up of slurry reactors for the photocatalytic oxidation of cyanide with TiO2 and silica-supported TiO2 suspensions - Marugán, Javier (2009)
A scaling-up methodology for the design of large-scale slurry reactors for the photocatalytic oxidation of cyanide is proposed. The only experimental information required to be determined at laboratory-scale is the intrinsic kinetics that describes the explicit dependence of the reaction rate with the local volumetric rate of photon absorption (LVRPA). Based on the kinetic model and the information about the geometry, irradiation source and the cyanide and catalyst concentrations as operation conditions, the performance of a larger scale reactor has been simulated following a predictive procedure with no adjustable parameters. The validation of the method has been carried out in a bench-scale reactor with ten times higher irradiated volume and a different geometry and irradiation source, in order to ensure that the conclusions about the applicability of the scaling-up model are independent of these parameters. The proposed scaling-up methodology and their correspondent procedures for the evaluation of the LVRPA distribution on the photoreactors has been successfully validated both with commercial TiO2 and a silica-supported TiO2 synthesized in our laboratory. The normalized root mean square error in the verification of the conversions predicted by the model for the larger scale reactor when compared with the experimental data are 7.7% and 6.2% for TiO2 and TiO2/SiO2, respectively.